Escolarização dos imigrantes italianos e seus descendentes em São João Del Rei - Minas Gerais (1888/1914) - Karina Fernandes Nicacio (2018)
This research seeks to understand the schooling process of children from Italian immigrant families in Minas Gerais that lived in the colonial nucleus created by the government in the city of São João del Rei (SJDR). The period of time that was investigated was the one between the end of the 19th century and the beginning of the 20th century, period in which that nucleus was created and emancipated, and the school was founded in that colony. In that period also the immigration policy started to be discontinued by the state of Minas Gerais because of the World War I. A lot of researches in the field of the History of Education have indicated that even though we can find some similarities between the dynamic of the schooling process of different immigrant groups, the way in which that process happened in each one of them was peculiar, depending on some factors. In that sense, to understand how it occurred with the investigated subjects, many aspects were considered such as the ethnical, the way that the immigrants established themselves in their new territory, characteristics of their home land and their school tradition. As we understand the schooling process in a wide sense, comprehending the educational context of Minas Gerais in the period of Brazilians First Republic was important to this investigation, so the policies of the state government and its actions to accommodate the immigrants children were investigated and also other possible groups working for their schooling process. In identifying the creation and establishment of an elementary and unisex school in José Theodoro colony a colonial nucleus territory by the state government in this investigation, the dynamic of this school operation was investigated, such as its spatial and material conditions, the process of occupation of the teachers post and the school practice by the prescription of the curriculums and methods in the teaching programs, inspectors reports and school books. Many sources were used to comprehend the schooling process of the investigated Italian immigrants children, like the legislation, school maps, inspectors reports, visit statements, reports from the colonial nucleus, president of states reports, records of the City Council of SJDR, correspondences, newspapers and school books. By this investigation, we have come to the conclusion that there are similarities between the schooling processes of the subjects of this research and the general population of Minas Gerais, specially the one living in the country area.